Reigniting compassion in healthcare: Manaakitia Reflective Rounds. Issue 6 (June 2017) - Shah, Shamsul; Lambrecht, Ingo; O'Callaghan, Anne
Abstract : Background: The reported levels of staff stress and burnout at all levels of training and disciplines is significant and recognised to impact on the care of patients and families. We present an initiative to support staff at Auckland City Hospital based on the Schwartz Center Rounds. Aim: To evaluate the efficacy of monthly case‐based, staff support reflective rounds to discuss complex emotional and psychosocial issues that arise in caring for patients and families. Methods: At Auckland City Hospital, a pilot programme called Manaakitia Reflective Rounds was conducted between April 2014 and September 2015. These were facilitated 1‐h, monthly, case‐based, staff support groups to discuss complex emotional and psychosocial issues in caring for patients. Staff evaluations and feedback were collated. Results: A total of 12 rounds was conducted exploring a range of challenging issues, from difficulty in achieving a patient's wish to die at home to coping with the 'heart sink' patient. There were 276 attendees in total, with an average attendance of 23 participants per round. A total of 218 evaluations was returned (79%) with rounds being rated as either exceptional or excellent by 87.5% of participants. Attendees reported positive benefits, such as gaining knowledge to help them care for patients (94%), working better with colleagues (87%) and gaining insight into how others think and feel in caring for patients (97%). Attendees reported a sense of having a 'shared experience' with better understanding of each other's professional perspectives and acknowledgement of the limitations (practical and human) in caring for patients and families. Conclusion: Evaluations of the rounds indicate a need for staff to have a safe and supportive space to explore the emotional aspects of their work. Staff particularly appeared to value having a 'shared understanding' with the recognition that they are 'not alone' when managing challenging situations.